Study protocol of a double-blind randomized control trial of transcranial direct current stimulation in post-stroke fatigue - Tang, Wai Kwong; Lu, Hanna; Leung, Thomas Wai Hong; Kim, Jong S.; Fong, Kenneth Nai Kuen (Frontiers in Neurology, 2024)
Rationale: Post-stroke fatigue (PSF) is a frequent problem in stroke survivors and often hinders their rehabilitation. PSF is difficult to treat, and pharmacological therapy is often ineffective. Transcranial direct current stimulation (tDCS) can modulate motor, sensory, cognitive and behavioral responses, as it alters neuronal activity by delivering a small amount of current via the scalp to the cortex, resulting in prolonged alterations to brain function. tDCS has been studied for the treatment of fatigue associated with other neurological diseases, namely, multiple sclerosis, Parkinson’s disease and post-polio syndrome. Aims: This proposed project will examine the effect of tDCS on PSF. Sample size estimates: We will recruit 156 participants aged 18 to 80 with chronic stroke and allocate them equally to two groups (i.e., n = 78 per group). Methods and design: This proposed project will be a double-blind randomized control trial. The participants will be randomly divided into two groups. The control group will receive sham tDCS, and the treatment group will receive active tDCS. The latter treatment will involve application of a constant 2-mA current via one 5 × 5-cm anodal electrode positioned on the scalp over the C3 or C4 positions (motor cortex) of the lesioned hemisphere and one cathodal electrode positioned at the ipsilateral shoulder in two 20-minute sessions per day for 5 days. The period of follow-up will be 4 weeks. Study outcome(s): The primary outcome measure will be a change in fatigue severity, as measured using the modified fatigue impact scale (MFIS). The participants’ scores on the MFIS ( total score and physical, cognitive and psychosocial subscores) will be collected before treatment (T0), after 10 treatment sessions, i.e., 1 day after the fifth treatment day (T1), and 1 week (T2), 2 weeks (T3) and 4 weeks (T4) thereafter. Both per-protocol analysis and intention-to-treat analysis will be performed. Discussion: This proposed project will provide proof-of-concept, i.e., demonstrate the benefits of tDCS for the treatment of PSF. The beneficiaries are the subjects participated in the study. This This will stimulate further research to optimize tDCS parameters for the treatment of PSF.